Hubungan Pengetahuan Ibu Tentang MP-ASI dengan Pemberian MP-ASI Dini di Wilayah Kerja Puskesmas Padasuka Cimahi - Rahmayanti, siti dewi; setianah, Ai; Apriyani, Dyna; Nurjanah, Nunung; Hastuti, Dwi (Faculty of Health Science and Technology, University of Jenderal Achmad Yani, 2023)
C Background: Complementary foods are foods and drinks other than breast milk that are given to infants when they are 6 months old. Giving food and drink other than breast milk to babies before 6 months of age is called early complementary feeding. The prevalence of infants who have been given early complementary foods in Cimahi city is 40%. Objective: The purpose of this research was to see the description of mothers knowledge, early complementary feeding, and the relationship between mothers knowledge and early complementary feeding in the working area of Padasuka Cimahi Health Center. Method: This study uses Analytical Survey research method with Cross Sectional design. The sample technique used was Total Sampling. The sample in this study were mothers who had babies aged 0-12 months totaling 92 mothers in the Padasuka Cimahi Health Center working area. Univariate analysis used frequency distribution and bivariate using Chi Square analysis. . The hypothesis test obtained is Ha accepted or failed to be rejected. Data collection methods using questionnaires. Results: The results of this study indicate that there is a relationship between maternal knowledge about complementary foods and early complementary feeding with the results of the Chi Square test with a p-value of 0.001 <0.05. Conclusion: There is a relationship between maternal knowledge about complementary foods and early complementary feeding. Suggestion: It is suggested that local health services can increase health promotion about complementary foods in the area to be used as additional information for mothers who are preparing to give complementary foods and who have given complementary foods to their babies, so that mothers can increase their knowledge of complementary foods.